THE HARU KINGDOM IN SUMATRA CROSSES THE AGES - Fadlin, Muh; Dewi, Heristina (Universitas Negeri Medan, 2019)
Through this paper, the authors examine the history of the existence of the Haru Kingdom on the east coast of northern Sumatra. This paper sketches the approach of history, using literary methods, source criticism, qualitative, and analytical descriptive. The theory used is change and continuity. This Haru Kingdom existed around the 13th to 16th centuries. Its territory covers the east coast of North Sumatra (now). This type of kingdom is Islam, but with a society that still shares animism. From those centuries we find historical records of the upheavals and wars in this kingdom. In addition, Aceh and Riau also include its influence in this Haru Kingdom.